2015
DOI: 10.4236/opj.2015.57021
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Therapeutic Applications of Optical and Thermal Response of SPION-Based Third Generation Plasmonic Nanodendrimers

Abstract: In this study, 9 nm superparamagnetic iron oxide nanoparticles (SPION) were functionalized by polyamidoamine (PAMAM) dendrimer. Using tetracholoroauric acid (HAuCl 4 ), magnetodendrimer (MD) samples were conjugated by gold nanoparticles (Au-NPs). Two different reducing agents, i.e. sodium borohydride and hydrazine sulfate, and pre-synthesized 10-nm Au-NP were used to evaluate the efficiency of conjugation method. The samples were characterized using X-ray diffractometry (XRD), transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…In our recent report [48], we indicated that all samples have a unique absorption peak in the range of 520-540 nm which reveals the formation of AuNPs. However, other peaks at 280 nm and 320 nm also correspond to Au-NPs aggregation [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…In our recent report [48], we indicated that all samples have a unique absorption peak in the range of 520-540 nm which reveals the formation of AuNPs. However, other peaks at 280 nm and 320 nm also correspond to Au-NPs aggregation [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…In our recent report, it was shown that the emission of FITC intensity is pH-dependent which can be considered as an advantage since tumors or infl amed tissues are relatively acidic, about 6.5, due to hypoxic conditions [25] thus, the fl uorescence intensity can be used as an easy monitoring probe. Also, it was recently reported by our group that SPION-based plasmonic nanodendrimers can have the potential capability to be utilized for thermal and bioimaging applications [26,27]. In this research, the results of synthesized SPIONs functionalized by fl uorescine isothiocynate (FITC) used as biomarker for fl uorescence imaging of L929 and MCF 7 cancer cell lines are described.…”
Section: Introductionmentioning
confidence: 95%
“…The former approach is more feasible due to the availability of hydrophilic layers, however, in order to produce sufficient temperature increase to destabilize the lipid layer to release the liposome content, large amount of MNPs should be used It is suggested by Liao et al [13] that Cetuximab-immunomicelles are a useful delivery vehicles for Dox and SPIO to epidermal growth factor receptor overexpressing tumor cells in-vivo and that it can serve as MRI-visible and targeted drug delivery. In some applications, MNPs are coated by gold layer to form a gold nanoshell (AuNS) for heating purpose rather than guidance [14][15][16]. AuNSs are very promising structures, which exhibit unique optical properties such as strong localized surface plasmon resonance (LSPR), surface-enhanced scattering, nonlinear optical properties, tunable resonance across the Vis-NIR due to adjustable nanoparticle size and shape [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%